IDDF2019-ABS-0293 A microbiome pilot study: the exploration of the gut-skin axis in hidradenitis suppurativa. (June 2019) - Lam, Suk Yee; Radjabzadeh, Djawad; Eppinga, Hester; van der Zee, Hessel H; Kraaij, Robert; Konstantinov, Sergey R; Fuhler, Gwenny M; Prens, Errol P; Thio, Hok Bing; Peppelenbosch, Maikel P
Abstract : Background: The concurrent occurrence of gut and skin diseases has led to the postulation of the existence of a gut-skin axis in which gut microbiota is thought to contribute to extra-intestinal skin manifestations. A dysbiotic skin microbiome has been demonstrated in the chronic inflammatory skin disease hidradenitis suppurativa (HS), but it remains unknown whether microbial disturbances of the gut are engaged in the complex pathogenesis. This study investigates the fecal microbiome in HS patients and healthy controls and explores the possibility of a gut-skin axis in HS. Methods: A total of 17 HS patients and 20 healthy controls provided a stool sample for 16S ribosomal RNA (rRNA) gene sequencing. A subset of axillary skin samples was available for concurrent microbial analysis of HS lesions (n=6), paired non-lesions (n=3) and healthy skin of controls (n=7). No oral antibiotics and no topical antibiotics/steroids were used in respectively eight weeks and seven days prior to sample collection. Results: The majority of 16S rRNA gene sequences at both the fecal and axillary skin sites were assigned to phyla Bacteroidetes, Firmicutes, Proteobacteria and Actinobacteria . Based on the overall bacterial community, two distinct clusters could be distinguished between the gut and the skin using principal coordinates analysis (PCoA). Furthermore, significant differences in bacterial composition were observed in fecal samples of HS patients when compared to healthy controls. However, we did not detect altered microbial signatures in the skin samples taken from HS lesions, non-lesions, and healthy controls. Conclusions: These findings indicate the presence of a distinct fecal microbiome in HS patients compared to healthy controls, suggesting the involvement of a gut-skin axis in the etiology of HS. Dysbiosis of the cutaneous microbiome in HS could not be confirmed here, but larger studies are warranted to further elucidate the role of microbiota as a potential part of the gut-skin axis in HS.